Radiologic imaging of acute pancreatitis - Glušič, Mojca (Radiology and oncology (Ljubljana), 2004)
Background. Acute pancreatitis comprises a broad spectrum of inflammatory changes in the gland and has a variety of causes. The most common are alcoholism and biliary tract disease. This paper discusses the current concepts of diagnosis and the relationship between morphology as depieted by imaging, pancreatic function tests and treatment planning. Conclusions. Our understanding of the morphologic changes produced by the inflammatory process has expanded in the last decade as more sophisticated imaging techniques have been used for evaluation.
Keywords: Absces; Abscess; Acute Disease; Akutna bolezen; akutni pankreatitis; Cholangiopancreatography, Endoscopic Retrograde; Complications; Diagnosis; diagnostika; Holangiopankreatografija endoskopska, retrogradna; Magnetic Resonance Imaging; Magnetna resonanca slikovna; Necrosis; Nekroza; Pancreatic Pseudocyst; Pancreatitis; Pankreatitis; Radiography; radiološka diagnostika; Tomografija radiografska, računalniška; Tomography, X-Ray Computed; trebušna slinavka; Trebušna slinavka, psevdocista